2016
DOI: 10.1021/acs.chemrestox.6b00347
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Computational Model for Androgen Receptor Activity

Abstract: Testing thousands of chemicals to identify potential androgen receptor (AR) agonists or antagonists would cost millions of dollars and take decades to complete using current validated methods. High-throughput in vitro screening (HTS) and computational toxicology approaches can more rapidly and inexpensively identify potential androgen-active chemicals. We integrated 11 HTS ToxCast/Tox21 in vitro assays into a computational network model to distinguish true AR pathway activity from technology-specific assay int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
235
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(238 citation statements)
references
References 35 publications
2
235
1
Order By: Relevance
“…In the present study, we confirmed that IL6 increases the transactivation potential of the AR; however, this effect was observed only in the presence of moderate to high androgen concentrations. In particular, we did not observe any IL6-mediated AR activation at 1 to 10 pmol/L of R1881, which is biologically comparable with castrate testosterone levels found in patients, considering the 10-to 100-fold higher transactivation capacity of R1881 (40,41). This is in contrast to several previous publications that have found androgen-independent effects of IL6 on AR activity.…”
Section: Discussionsupporting
confidence: 60%
“…In the present study, we confirmed that IL6 increases the transactivation potential of the AR; however, this effect was observed only in the presence of moderate to high androgen concentrations. In particular, we did not observe any IL6-mediated AR activation at 1 to 10 pmol/L of R1881, which is biologically comparable with castrate testosterone levels found in patients, considering the 10-to 100-fold higher transactivation capacity of R1881 (40,41). This is in contrast to several previous publications that have found androgen-independent effects of IL6 on AR activity.…”
Section: Discussionsupporting
confidence: 60%
“…MDA-kb2 cells express 240 fmol AR/mg-protein and are stably transfected with a luciferase construct driven by a steroid response element (Hall et al, 1990;Ham et al, 1988;Wilson, Bobseine and Gray, 2004). The assay is included in Tox21 and ToxCast (Kleinstreuer et al, 2017). No toxicity was evident at the concentrations tested (Supplemental Material, Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…For endocrine‐disrupting potential, we evaluated four main processes, including androgen, estrogen, thyroid, and steroidogenic. For androgen, we utilized androgen receptor (AR) pathway activity integrated from 11 AR‐related in vitro HTS ToxCast assays and considered compounds with area under the curve (AUC) of ≥0.1 to be active in at least one AR pathway assay (active, inactive) . For estrogen, we utilized estrogen receptor (ER) interaction scores integrated from 13 ER‐related in vitro ToxCast assays and considered compounds with an AUC score of ≥0.1 to be active in at least one ER pathway assay (active, inactive) .…”
Section: Methodsmentioning
confidence: 99%
“…For androgen, we utilized androgen receptor (AR) pathway activity integrated from 11 AR-related in vitro HTS ToxCast assays and considered compounds with area under the curve (AUC) of ≥0.1 to be active in at least one AR pathway assay (active, inactive). 37 For estrogen, we utilized estrogen receptor (ER) interaction scores integrated from 13 ER-related in vitro ToxCast assays and considered compounds with an AUC score of ≥0.1 to be active in at least one ER pathway assay (active, inactive). 38 For thyroid, we utilized the results from the in vitro Amplex UltraRed-thyroperoxidase or thyroid peroxidase (AUR-TPO) assay 39 and a thyroid-specific in vitro HTS ToxCast assay.…”
Section: Data Sources Of Endocrine-disrupting Potential or Neurotoxmentioning
confidence: 99%